Knowledge and Perception of Self-Medication of Cough Medication in Pedicab Drivers in Surabaya - Amelia Lorensia; Rivan Virlando Suryadinata; Melly Eva Idamayanti; Gora Dirga Kusuma; Nyoman Yoga Diputra (Indonesian Journal of Pharmaceutical Science and Technology, 2022)
Pedicab drivers who are exposed to pollution and have a smoking habit are at high risk of developing COPD (chronic obstructive pulmonary disease). The initial disturbance that occurs is a decrease in lung function which often causes complaints of cough symptoms. A person's knowledge and perception can influence how the pattern of self-medicating cough treatment so far. The purpose of this study was to determine the knowledge and perception of Self-medication of cough medicine. The research design was cross-sectional. The material of this research was in the form of information from subjects using direct questions and answers (interviews) with knowledge and perceptions of self-medicating cough medicine questionnaire. This research was conducted from September to December 2018 and used descriptive data analysis. The respondents involved were 163 peoples. Most respondents had a low level of knowledge of self-medication of cough medicine (97 of 163). The results of perception of self-medication of cough medicine indicated that most respondents had negative level (78 of 163). There was a relationship between knowledge and perception about self-medication of cough medicine (p=0.006). The proper health education strategy by increasing knowledge can also improve perceptions of self-medicine of cough medicine.